Application of rough set theory on factors analysis of influencing the grain output - XIANG Li-guo; SHENG Yi-ming; HE Yong; YU Xin-jie (浙江大学学报. 农业与生命科学版)
There are many influential factors which jointly determine the output of grain production. Applying the basic principles of rough set theory to data analysis and decision, this paper analyzes the output of grain system in Zhejiang province. The dominant factors have been found out, which are considered to provide a scientific basis for policy decision and rationalized management in planned grain production.